Transforming EFL Students' Narrative Writing Through Gamification - Manthofani, Mochamad Thirta; Saifulloh, Ahmad Iklil; Lindawati, Rini (Philosophiamundi, 2024)
Current EFL pedagogy lies in the limited use of innovative techniques like gamification, which has the potential to significantly enhance students' narrative writing skills. This study investigates the effectiveness of gamification in improving EFL students' ability to write narrative texts, grounded in motivational and engagement theories. Employing a quasi-experimental pretest-posttest design, data were collected from two groups of students: a control group using conventional methods and an experimental group utilizing gamification elements such as points, badges, and challenges. The findings reveal that students exposed to gamification demonstrated superior narrative writing skills compared to the control group. These results suggest that integrating gamification in EFL writing instruction can substantially boost student motivation and engagement, leading to improved narrative writing performance.